Perancangan Prototipe Turbin Angin Sumbu Horizontal Skala Laboratorium Dengan Inverter - Najma Safienatin Najah; Arief Muliawan; Febria Anita (Jurnal Teknik Juara Aktif Global Optimis, 2021)
A horizontal axis wind turbine design research has been carried out using an inverter. This study aims to generate the output power generated by the generator through an inverter. So that the use of an inverter can turn on the 10 watt lamp. From the research results obtained turbine rotation varied between 1357 rpm to 2415 rpm producing a generator voltage of 3.05 volts to 4.61 volts and generator currents 32mA up to 49 mA. The inverter produces a voltage of 16.57 volts up to 20.46 volts and an inverter current of 0.60 amperes up to 0.48 amperes. The greater the rotation of the wind turbine turbine, the greater the generator voltage generated and so is the voltage of the inverter. While the current will increase as the turbine rotation increases and the inverse of the inverter current will decrease as the turbine rotation increases.